Effects of Reading Skills on Students’ Performance in Science and Mathematics in Public and Private Secondary Schools - Ombra A. Imam (Intelektual Pustaka Media Utama, 2016)
In the Philippine education system, reading, mathematics, and science formed part of the core areas of basic education curriculum. For the last decade, the quality of Philippine education was put into a big question due to poor performance of students in mathematics and science tests both local and abroad. The initial result of current efforts of the government by adopting K-12 curriculum didn’t do much to change the status quo. The purpose of this study is to determine the reading predictors of students’ performance in Mathematics and Science and identify its effects to such performance. A total of 660 freshmen students from public and private high schools in Cotabato City, Philippines were taken as sample. A validated and reliable 150-item test in reading comprehension skills, mathematics and science was used to get primary data to perform correlation and regression analysis. Findings showed that only making inference and getting main idea were predictors of mathematics performance of students in public school and private schools, respectively. Data analysis also revealed that two reading skills such as noting details and making inference had an influence on science performance of students in public school while skills in getting main idea and drawing conclusion influenced science performance of students in private schools. However, there was only one skill such as vocabulary in context which was predictor of overall science performance of all students. Moreover, separate effects of making inference, identifying main idea explained only 1.8 percent and 1.3 percent of students’ math performance while their combined effects provided only .1 percent or nearly zero percent. Furthermore, the study found out that separate effects of noting details contributed 3.3 percent and its combined effects with making inference explained 4.2 percent of science performance of students in public schools. In terms of effects of reading to science performance in private schools, making inference provided 1.2 percent of separate effect; making inference and drawing conclusion influenced 2.8 percent of combined effect; understanding vocabulary in context has overall one percent of separate effect.